Language shift from Afrikaans to English in "Coloured" families in Port Elizabeth three case studies - Fortuin, Esterline Diane (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (General Linguistics))--University of Stellenbosch, 2009.